Comparative Proteomic Profiling Using Two-Dimensional Gel Electrophoresis and Identification via LC-MS/MS Reveals Novel Protein Biomarkers to Identify Aggressive Subtypes of WHO Grade I Meningioma - Osbun, Joshua W.; Tatman, Philip D.; Kaur, Sumanpreet; Parada, Carolina; Busald, Tina; Gonzalez-Cuyar, Luis; Shi, Min; Born, Donald E.; Zhang, Jing; Ferreira, Manuel (Journal of Neurological Surgery Part B: Skull Base, 2017)
Background Meningomas represent the most common primary intracranial tumor. The majority are benign World Health Organization (WHO) Grade I lesions, but a subset of these behave in an aggressive manner. Protein biomarkers are needed to distinguish aggressive from benign Grade I lesions.Materials and Methods Pooled protein lysates were derived from five clinically aggressive Grade I and five typically benign WHO Grade I tumors snap frozen at the time of surgery. Proteins were separated in each group using two-dimensional gel electrophoresis (2DGE) and protein spots of interest were identified using liquid chromatography–mass spectrometry (LC-MS). Potential biomarker candidates were validated using western blot assays in individual tumor samples and by tissue microarray (TMA).Results Seven candidate biomarkers were obtained from the 2DGE and validated via western blot and TMA. Biomarker validation data allowed for the creation of predictive models using binary logistical regression that correctly identified 85.9% of aggressive tumors within the larger cohort of Grade I meningioma.Conclusion Simple protein separation by 2DGE and identification of candidate biomarkers by LC-MS allowed for the identification of seven candidate biomarkers that when used in predictive models accurately distinguish aggressive from benign behavior in WHO Grade I meningioma.
Keywords: meningioma; proteomic; two-dimensional gel electrophoresis; mass spectrometry; biomarker discovery